PCSK9 inhibitors attenuates arterial stiffness in patients with acute coronary syndrome: PCSK9 Inhibitors Reduce Arterial Stiffness in Acute Coronary Syndrome - Wang, Liang; Wang, Ruijie; Jiao, Tiantian; Xu, Linghao; Ji, Endong; Jiang, Yuanzhen; Wang, Yuanqi; Liu, Yehong; Li, Jiming (Journal of Medical Biochemistry, 2025)
Background: This study aimed to evaluate the effects of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors on arterial stiffness in patients with acute coronary syndrome and atherosclerosis, an area that has not been extensively explored. Methods: Patients were randomly divided into two groups: one group received statin therapy combined with PCSK9 inhibitors (Evolocumab or Alirocumab), while the other group received statins alone. Indicators of lipid metabolism and arterial stiffness were measured at baseline, 1 month, and 6 months after treatment initiation. Results: After 1 month, the group treated with statins and PCSK9 inhibitors showed significantly greater reductions in LVEF, NTP, TC, TG, LDL, and Lp(a) levels compared to the statin-only group. By the 6-month follow-up, pulse wave velocity showed marked improvement (p < 0.05), and ankle-brachial index was also significantly reduced in the combination treatment group (p < 0.05). No significant differences were observed between Evolocumab and Alirocumab (p > 0.05). Conclusions: The findings suggest that PCSK9 inhibitors not only improve lipid metabolism but also reduce arterial stiffness, supporting their use in treating vascular disorders in patients with acute coronary syndrome and atherosclerosis.